Oxidation resistance of TiAlN/ZrN multilayer coatings. (May 2016) - Lei, Zhefeng; Liu, Yashan; Ma, Fei; Song, Zhongxiao; Li, Yanhuai
Abstract: TiAlN/ZrN multilayered coatings with the modulation ratio (the thickness ratio of sub-layer A and sub-layer B) changing from 1:1 to 1:3 were deposited by multi-arc ion plating technology. Air-annealing at 500 °C and 800 °C were conducted to evaluate the oxidation resistance of the coatings. X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), and Vickers Indenter were adopted to characterize the microstructure and mechanical properties of the coatings. The results show that the M-30 sample with a minimum modulation period (the total thickness of sub-layer A and sub-layer B) of 65 nm and a modulation ratio of 1:1 exhibits a coherent hardening effect as a result of coherent growth between the inter-layers. Furthermore, the multilayer-structure was kept in M-30 sample after annealing at 800 °C in air, but M-50 sample with a modulation period of 85 nm was delaminated, and M-100 sample with a modulation period of 135 nm even peeled off. Highlights: Coherent hardening and excellent oxidation resistance were observed in TiAlN/ZrN multilayer coatings. When the modulation period was less than 100 nm, multilayer structure still kept compact after annealing at 800 °C in air. Spinodal decomposition and interface diffusion had occurred successively during the annealing process at 800 °C. The improvement of oxidation resistance is result from the combined action of reduction of Zr and enhancement of interface.